Interpretations of Verses about Islamic Criminal Law and its Polemics in Indonesia’s Positive Law - Hasep Saputra; Nurma Yunita; Ainal Mardhiaturrahman; Wina Purnamasari (Institut Agama Islam Negeri (IAIN) Curup, 2021)
This study was conducted to find out the interpretations of Islamic criminal law verses and to see the polemics which occurred in the applications of Islamic criminal law in Indonesia alongside the harmonization of its applications in Indonesia. This study used a normative-descriptive approach in a way that explained in detail the laws and the verses’ interpretations as well as the polemics of Islamic criminal law in the Indonesia’s positive law. In the context of the development and application of national law in Indonesia, Islamic law is one of the sources adopted. Islamic law itself regulates the vertical relationship with Allah and the relationship with humans. These two relationships have a role in the formation of national law in Indonesia. In terms of applications, Islamic law can contribute to the development of positive law with the following three alternatives: 1) Islamic law which is a continuation of legal politics in the colonial period, either through transitional rules of the 1945 Constitution’s article 2 or by means of being stipulated in the further new legislation, 2) positive Islamic law which is sourced from Islamic values, and 3) the theory of legal leveling. This theory is applied to make Islamic law a source of national law in the future.